Novel insights into whey protein differences between donkey and bovine milk. (15th December 2021) - Li, Mohan; Yu, Haikun; Chen, Jiali; Abdlla, Rayhnigul; Liu, Aicheng; Song, Wanying; Zhang, Juan; Zhang, Xiumin; Yue, Xiqing; Li, Qilong
Highlights: 989 and 1534 whey proteins were characterized in donkey and bovine milk. 623 common whey proteins were found in both groups. 229 differentially expressed whey proteins (DEWPs) were identified. GO Ontology and metabolic pathways analysis of these DEWPs were performed. Abstract: In this study, we characterized and compared the whey proteins from donkey and bovine milk using HPLC-MS/MS-based proteomics. A total of 989 and 1534 whey proteins were characterized in donkey and bovine milk, respectively. Furthermore, 623 whey proteins were found in both groups, and 229 differentially expressed whey proteins (DEWPs) were identified. Among the common proteins, 66 DEWPs were upregulated and 163 were downregulated in donkey milk compared to those in bovine milk. Gene Ontology analysis revealed the cellular components, biological processes, and molecular functions of these DEWPs. Metabolic pathway analysis suggested that most DEWPs were associated with endocytosis, platelet activation, and phagocytosis. These results improve our understanding of the differences between donkey and bovine whey proteins and provide important information regarding these proteins as nutritional and functional factors in dairy product formulations from multiple milk sources.